2017
DOI: 10.1111/ppl.12623
|View full text |Cite
|
Sign up to set email alerts
|

Increased contribution of wheat nocturnal transpiration to daily water use under drought

Abstract: Increasing evidence suggests that in crops, nocturnal water use could represent 30% of daytime water consumption, particularly in semi-arid and arid areas. This raises the questions of whether nocturnal transpiration rates (TR ) are (1) less influenced by drought than daytime TR (TR ), (2) increased by higher nocturnal vapor pressure deficit (VPD ), which prevails in such environments and (3) involved in crop drought tolerance. In this investigation, we addressed those questions by subjecting two wheat genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 30 publications
(59 reference statements)
1
11
1
Order By: Relevance
“…Therefore, our data could not confirm the effect of plant physiological changes due to higher temperatures on transpiration during night that were reported in other studies such as increased cuticular transpiration and incomplete stomatal closure (e.g. Claverie et al, 2017). ET N rates during dusk, nocturnal, and dawn also differed between hot and normal days, but no consistent change in the dynamics of the nighttime ET that could be linked to plant physiological reactions was observed.…”
Section: 1029/2018wr024072contrasting
confidence: 90%
“…Therefore, our data could not confirm the effect of plant physiological changes due to higher temperatures on transpiration during night that were reported in other studies such as increased cuticular transpiration and incomplete stomatal closure (e.g. Claverie et al, 2017). ET N rates during dusk, nocturnal, and dawn also differed between hot and normal days, but no consistent change in the dynamics of the nighttime ET that could be linked to plant physiological reactions was observed.…”
Section: 1029/2018wr024072contrasting
confidence: 90%
“…Various studies have shown that night-time transpiration can be significant (e.g., Caird et al, 2007b;Gleason et al 2017;Claverie et al 2018). In agreement with this, it was observed that night-time transpiration accounted for 8-12% of total daily transpiration under optimal soil water supply.…”
Section: Root Mediated Hydraulic Redistributionsupporting
confidence: 58%
“…Nocturnal stomatal conductance (observed after dark acclimation) was significantly different between individuals, suggesting differences in the regulation of water loss during the night period. Nocturnal transpiration is involved in essential physiological processes such as nutrient transport (Zeppel et al , 2014) and could represent 30% of daytime water consumption in crops (Claverie et al , 2018). The initial g sw values observed here under dark conditions represented up to ~10% of the value reached under the light period, confirming its importance for the regulation of plant water budget.…”
Section: Discussionmentioning
confidence: 99%